PROVOCATION, SACRILEGE, INTERTEXTUALITY: STRATEGIES OF (AUTO)MYTHOLOGIZATION IN THE CREATIVE WORKS OF SAVA DAMJANOV - Tatarenko, Ałła (Porównania, 2019)
In the article we examine the postmodern strategies of (auto)mythologization in the creative work of a well-known Serbian writer, Sava Damjanov. Constituent parts of this strategy include intellectual provocation, creation of a personal literary world and myth combined with apocryphal, ironical (sometimes on the verge of sacrilege) treatment of “great narratives” and national myths, and with intertextuality (including autocitations). Special attention is paid to the strategies of autorepresentation (textual and visual) and to the strategies of leveling the frontiers between “real” and literary reality (the use of erotic code both in textual and in visual form, the leveling of frontiers between textual and corporal codes, between fictional and autobiographical, between the writer’s body and his works).